2012
DOI: 10.2480/agrmet.68.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Atmosphere-rice paddy exchanges of inorganic particles and relevant gases during a week in winter and a week in summer

Abstract: The aim of the present study was to investigate the air concentrations (mass concentration) and exchange fluxes of inorganic particles, i.e., water-soluble inorganic components in fine and coarse particles, and relevant gases at a paddy field for the single cropping of rice in central Japan. The target chemical species were ammonium (pNH 4 ), nitrate (pNO 3 ), nitrite (pNO 2 ), sulfate (pSO 4 ), and chloride (pCl) for inorganic particles separated into coarse and PM2.5 fractions and ammonia (NH 3 ), nitric aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The study site is situated in a rural area typical of this region, composed of arable land (mainly rice paddies), small forests, and residential areas. Single cropping of rice is performed in this region, and the typical management practices have been described in Hayashi et al (2012). The periods of cropping and fallow seasons in the study period from May 2007 to April 2011 are listed in Table 1 together with the mean air temperature and the total precipitation during each period.…”
Section: Site Description and Field Managementmentioning
confidence: 99%
See 3 more Smart Citations
“…The study site is situated in a rural area typical of this region, composed of arable land (mainly rice paddies), small forests, and residential areas. Single cropping of rice is performed in this region, and the typical management practices have been described in Hayashi et al (2012). The periods of cropping and fallow seasons in the study period from May 2007 to April 2011 are listed in Table 1 together with the mean air temperature and the total precipitation during each period.…”
Section: Site Description and Field Managementmentioning
confidence: 99%
“…Therefore, it is possible that the role of Japanese paddy fields as a sink of atmospheric NH 3 has recently increased. Hayashi et al (2012) demonstrated the importance of NH 3 in the atmosphere-rice paddy exchange through intensive observations over two weeks. Long-term monitoring is required to elucidate the seasonal patterns and the annual balance of atmosphere-rice paddy exchanges of NH 3 .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The EC technique enables us to quantify not only ET but also fluxes of greenhouse gases such as CO 2 , CH 4 , and N 2 O and even NH 3 (Hayashi et al, 2013) and pSO 4 (Hayashi et al, 2012) in combination with the improved aerodynamic method (Miyata et al, 2000). Nevertheless, real-time flux monitoring by the EC technique remains challenging, because the final fluxes must be extracted from large turbulent fluctuation datasets, demanding large computational resources.…”
Section: Introductionmentioning
confidence: 99%